Seasonal Variations in Sugar and Protein Contents of Halophytes in Indian Desert - Mohammed, Sher; Sen, Davis N (Annals of Arid Zone, 2016)
Seasonal changes -in sugar and protein contents of some important halophytes in Indian desert have been studied and presented here. Plants at Jodhpur (site-II), which is non-saline, showed maximum sugar during summer season. Plant species at Pachpadra (site-I), which is extremely saline, indicated higher sugar during rains, when soil salinity is reduced. Crude protein declined under drought or saline stress at both sites. Plant species at site-II exhibited higher crude protein as compared to those at site-I.